Warming up for intermittent endurance sports - Cone, J. R. (Strength and Conditioning Journal, 2007)
The warm-up serves several functions: a) preparation for training and competition, b) injury prevention, and c) developing athleticism and sport performance. A warm-up specific to intermittent endurance sports should target 2 components crucial to competition and training: a) the physiological preparation for work, and b) the physical preparation for movement demands of the sport. The purpose of this article is to examine the components of a warm-up specific to intermittent endurance sports and the implementation of an appropriate warm-up integrating flexibility and speed components.